USING MATHEMATIC-STATISTICAL METHODS IN MEDICAL RESEARCH FOR RAPID DIAGNOSIS - Sayfullaeva Dilbar Izzatillaevna (Web of Journals Publishing, 2025)
To identify patterns and relationships between various indicators in medicine, it is necessary to apply specific methods of processing experimental data, as well as to have knowledge of the fundamentals of biometrics and mathematical statistics. Statistics in medicine is one of the key tools for analyzing experimental data and clinical observations, as well as the language through which mathematical results are communicated. The mathematical framework is widely used for diagnostic purposes, solving classification problems, and discovering new patterns, as well as for formulating new scientific hypotheses. The use of statistical software requires knowledge of the fundamental methods and stages of statistical analysis, including their sequence, necessity, and sufficiency.
Keywords: Medical experiment, statistics, database, mathematical data processing, chi-square, modern clinical practice, disease development prediction.